The safety and efficacy of the re-administration of gilteritinib in a patient with FLT3-mutated R/R AML with CNS relapse: a case report - Ji, Yueru; Wan, Zhuo; Yang, Jian; Hao, Miaowang; Liu, Li; Qin, Weiwei (Frontiers in Oncology, 2024)
In this case report, we have reported that gilteritinib shows significant therapeutic effects on a R/R AML case remained refractory to prior treatment with sorafenib, multiple lines of intensive chemotherapy and HSCT. Experienced newly diagnosed AML 3 year ago and CNS relapse followed up for 23 months, the patient has sustained BM remission status with MRD negative after treated with gilteritinib. The positive anti-leukemic effect of gilteritinib may bring new hope for the treatment of FLT3 mutated AML with CNS relapse.